Resolubilidade local para duas classes de campos de vetores suaves complexos - Nunes, Luciele Rodrigues (2016)
This work study complex linear partial differential operators of order one without having terms of zero order (complex vector fields). We have established a necessary and suficient condition for local solvability of a class of operators which are not elliptic precisely in a 1-dimensional submanifold and we construct solutions for a class of operators satisfying the condition (P) and which are not elliptic precisely in a point.